NUMERICAL METHOD APPROACH TO ANALYSIS OF DRAINAGE CHANNELS OF PIT-3 WEST BANKO TANJUNG ENIM - Arif Satria Rusmana; Achmad Syarifudin; Henggar Risa Destania (Indonesian Journal of Engineering and Science (IJES), 2022)
The drainage network system should be designed to accommodate normal flow rates, especially during the rainy season. This means that the capacity of the drainage channel has been calculated to accommodate the water discharge that occurs so that the area in question does not experience puddles or the channel can to be function properly. For this reason, research is needed to analyze the ability of the ex-coal mine drainage channel in PIT-3 West Banko Tanjung Enim. The research was carried out with the help of the HEC-RAS software program to see the changes in the water level in the drainage channel where the water was overflowing from the channel body. The results showed that all the section profiles of the drainage channel (P1) till (P10) were still in the safe condition or the channel was still stable (stable channel).